Construction of α-Fe2O3 and Fe/Co-N4 structures with faceted TiO2 nanocrystals for highly efficient degradation of sulfathiazole in water. (20th May 2019) - Gao, Zhao; Yang, Hanpei; Mao, Jingtao; Wu, Junming
Abstract : The severe pollution and scarcity of clean water occurred worldwide. The photocatalysis on semiconductors is highly expected in decontamination or purification of water, although the performance of current semiconductors is extremely restricted by the low efficiency in utilization of sustainable solar energy. An effective strategy for this restriction is the construction of their surface heterojunctions. Unfortunately, the constructed heterojunctions have to be heterotypic because of the band discontinuities at the isotypic interface. Moreover, in most of cases, the constructing does not necessarily improve their performance efficiently due to the inertness of the ground state oxygen in trapping of the separated electrons. In this work, well-faceted TiO2 with coexposed (001) and (101) and selective deposition of α-Fe2 O3 and Fe/Co-N4 on the (001) facets was acquired. The overall photocatalytic activity of the well-designed composite in degradation of sulfathiazole has enhanced significantly by as much as 5.91 times compared to the bare faceted TiO2, and remained almost the same in 40 recycle usages. The significant performance of the designedly constructed composite was attributed to the remarkably enhanced light absorption, efficient separation of photo-induced charge carriers, oxygen activation and trapping of separated electrons through the Fe/Co-N4 structure and the n-p-n dual heterojunction. Graphical abstract: A designedly constructed photocatalyst with α-Fe2 O3 and Fe/Co-N4 selectively deposited on (001) facets of TiO2 was obtained, synergy in light harvesting, charge separation and oxygen activation was acquired for utilization of sustainable solar energy and oxygen in air, significant performance in STZ degradation was achieved.Image 1 Highlights: Selective deposition of α-Fe2 O3 and Fe/Co-N4 on (001) facets of TiO2 was acquired. Significant performance of constructed photocatalyst in sulfathiazole degradation was achieved. A synergy in light harvesting, charge separation and oxygen activation in photocatalysis was proposed. Activation of oxygen in efficient trapping of separated electrons for producing of superoxide radicals is necessary.